The Meaning of The Madura Proverb "Bhuppa’-Bhâbhu’-Ghuru-Rato" in Hasan Hanafi's Social Theology Perspective and Its Relevance to Community Development - Anam, Rifqi Khairul (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research investigates the renowned adage Bhuppa'-Bhâbhu'-Ghuru-Rato in Madura through the lens of Hasan Hanafi's social theology. This study is based on library research. Hasan Hanafi's social theology is employed as a formal object with the goal of reconstructing theology as a social basis rather than an empty religious dogma, so that faith might have a practical purpose as a foundation for human ethics and motivation. Hasan Hanafi's social theology, which is pertinent to Islam in Madura as well as the worldwide spirit of Islam Nusantara, which depicts Islam as rahmah li al-'alamin, is accurate. Islamic concepts that apply broadly in society. Madura culture must first obey their parents, followed by the teachers, eventually the leaders. This indicates that in Madura's socio-cultural life, there are reference standards for the principal figures in a hierarchy that should be followed.